Characterization of the complete chloroplast genome sequence of Cardamine lyrata Bunge(Brassicaceae). Issue 6 (3rd June 2022) - Xu, Xinhan; Yao, Xuan; Zhang, Caijuan; Xia, Pengguo
Abstract: Cardamine lyrata Bunge 1833 grows near paddy fields, streams and shallow water. Its young stems and leaves can be eaten. It can also be used as medicine and has the effect of clearing away heat and dampness. The complete chloroplast genome sequence of the C. lyrata was determined and assembled. The complete genome is 155, 170 bp in length, including a large single-copy region (LSC) of 84, 270 bp, a small single-copy region (SSC) of 17, 918 bp and two copies of inverted repeat (IR) regions of 26, 491 bp. The overall GC content of C. lyrata is 36.2%. The genome of C. lyrata contains 131 genes, including 85 protein-coding genes (PCGs), 37 tRNAs, and 8 rRNAs. Phylogenetic analysis suggested that the ten species in Cardamine were clustered together into a single branch within the Brassicaceae family and C. amariformis is at the base of the tree and C. lyrata and C. fallax are sister groups of the inner clade.